A future for the past: Petrie's Palestinian collection; an exhibition held in the Brunei Gallery : essays and exhibition catalogue - Sparks, Rachael Thyrza; Laidlaw, Stuart (Institute of Archaeology, University of London, 2007)
Flinders Petrie and the archaeology of Palestine / Rachael Thyrza Sparks -- A history of the Petrie Palestinian Collection / Rachael Thyrza Sparks and Peter J. Ucko -- Representation and identity / Peter J. Ucko -- The liberating power of archaeology : changing aims and directions in archaeology / Fekri Hassan -- Heritage pilgrimage : ancestors, amulets and olive branches / Beverley Butler